PROFESSIONAL COMPETENCE OF PRIMARY EDUCATION TEACHERS - Mirzahmatov B. B. (Modern American Journals, 2025)
The professional competence of primary education teachers requires skills from this teacher. It depends on his experience, qualifications, how much he loves children and teaches them. What is required of a teacher in raising a child to be mature is to work hard and teach the child.
Keywords: Primary education, teacher, professional skills, competence, salary and financial benefits, professional development opportunities, social protection, working conditions, professional recognition and appreciation.